The role of language in knowledge sharing within multinational corporations : Focus on individuals in multinational teams - Rokama, Kasper (My University, 2022)
Knowledge sharing is a prerequisite for a functioning organization and a competitive advantage for those who are able to do it effectively. Multinational corporations with their globally dispersed organizational structure are in a privileged position to achieve this. However, in order to share knowledge effectively they must fully understand the implications of language use for the individual employee as well as for entire multinational teams. The purpose of the thesis is to understand how language influences knowledge sharing within multinational teams. This is done by first examining the study of language in international business, namely from the perspectives of language proficiency, language-induced emotions, and communication behaviour. Theories of social identity and self-categorization are employed to facilitate further understanding of related phenomena such as language-based grouping and power dynamics. Subsequently, multinational team members from five different MNCs are interviewed. Qualitative methodology was adopted in conducting the research. The interviews were carried out virtually in the spring of 2022. Thematic analysis was utilized to process and analyze the collected data in order to uncover the varied roles that language plays in knowledge sharing at the higher organizational levels of multinational corporations where multiple languages are habitually used. Reflected against the accrued understanding, the findings of the thesis suggest that high language proficiency among multinational team members is associated with fewer communication difficulties and reduced frequency and intensity of negative language-induced emotions, although perceived and real relative differences in language skills can evoke these emotions regardless of one’s relatively superior or inferior proficiency. Nevertheless, non-native speakers with high language proficiency have the propensity to act as liaisons and facilitate understanding for linguistically less proficient members by adopting communication behaviours that are directed at enhancing knowledge sharing.

Tiedon jakaminen on edellytys organisaation toiminnalle sekä kilpailuetu niille, jotka pystyvät tekemään sen tehokkaasti. Monikansalliset yritykset, joiden organisaatiorakenne on hajautettu maailmanlaajuisesti, ovat erityisasemassa tämän saavuttamiseksi. Tätä varten niiden on kuitenkin ymmärrettävä kielenkäytön vaikutukset sekä yksittäiseen työntekijään että kokonaisiin monikansallisiin tiimeihin. Tämän pro gradu -tutkielman tarkoituksena on ymmärtää, miten kieli vaikuttaa tiedon jakamiseen monikansallisissa tiimeissä. Tämä toteutetaan tarkastelemalla ensin kielten tutkimusta kansainvälisessä liiketoiminnassa, erityisesti kielitaidon, kielenkäyttöön liittyvien tunteiden sekä viestintäkäyttäytymisen näkökulmista. Lisäksi sosiaalisen identiteetin ja itsekategorisoinnin teorioita hyödynnetään tutkimusaiheeseen liittyvien ilmiöiden, kuten kieliperusteisen ryhmäytymisen ja valtadynamiikan ymmärtämisessä. Tutkielman aineiston keruu toteutetaan haastattelemalla monikansallisten tiimien jäseniä viidestä eri monikansallisesta yrityksestä. Tutkimus toteutettiin laadullisesti. Haastattelut suoritettiin virtuaalisesti keväällä 2022. Kerätty aineisto käsiteltiin ja analysoitiin hyödyntäen temaattista analyysia. Näin voitiin havainnoida, millainen rooli kielellä on tiedon jakamisessa monikansallisten yritysten ylemmillä organisaatiotasoilla, joissa useiden kielten käyttö on tavallista. Pro gradu -tutkielman tulokset viittaavat siihen, että monikansallisten tiimien jäsenten korkea kielitaito on yhteydessä vähäisempiin kommunikaatiovaikeuksiin ja vähäisempään kielenkäyttöön liittyvien kielteisten tunteiden esiintymistiheyteen ja -voimakkuuteen. Koetut ja todelliset suhteelliset erot kielitaidossa voivat kuitenkin herättää näitä tunteita riippumatta siitä, onko kielitaito suhteellisesti parempi vai huonompi. Lisäksi kielitaitoiset muut kuin äidinkielen puhujat ovat taipuvaisia toimimaan yhteyshenkilöinä ja helpottamaan kielitaidoltaan heikompien jäsenten ymmärtämistä omaksumalla viestintäkäyttäytymistapoja, jotka kohdistuvat tiedonjaon tehokkuuden parantamiseen.
Keywords: language, emotions, communication behaviour, knowledge sharing